Does increased migration affect the rural–urban divide in suicide? A register‐based repeated cohort study in Sweden from 1991 to 2015. Issue 1 (27th July 2021) - Kanamori, Mariko; Kondo, Naoki; Juárez, Sol P.; Cederström, Agneta; Stickley, Andrew; Rostila, Mikael
Abstract: Some countries have high suicide rates in rural areas with a potentially stronger impact of rural context on foreign‐born residents. In Sweden, where immigration has been increasing, dispersion policies have directed refugees/migrants to settle in rural areas. We examined whether trends in suicide mortality vary by nativity and rurality. A repeated cohort study was designed using Swedish national register data between 1991 and 2015. Our three‐level analysis found that male suicide rates in rural areas were 1.2 times higher than in urban areas, with the rate decreasing over time in both urban and rural areas. We observed fluctuations in suicide mortality among foreign‐born men residing in small rural communities, with high suicide rates in the 2000s. The proportion of unemployed was linked to the excess rate of suicide in rural municipalities. Dispersion policies moving migrants to rural areas should take into account the regional characteristics both within municipalities (e.g., income distribution) and between municipalities (e.g., labour market characteristics).